2009
DOI: 10.1161/circulationaha.108.785014
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Thrombosis and Anticoagulation Therapy in Cardiac Amyloidosis

Abstract: Background-Primary amyloidosis has a poor prognosis as a result of frequent cardiac involvement. We recently reported a high prevalence of intracardiac thrombus in cardiac amyloid patients at autopsy. However, neither the prevalence nor the effect of anticoagulation on intracardiac thrombus has been evaluated antemortem. Methods and Results-We studied all transthoracic and transesophageal echocardiograms of cardiac amyloid patients at the Mayo Clinic. The prevalence of intracardiac thrombosis, clinical and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(180 citation statements)
references
References 39 publications
4
158
0
18
Order By: Relevance
“…16, 17 Feng et al reported that AF, poor left ventricular diastolic function were independently associated with increased risk for intracardiac thrombosis in patients with amyloidosis. 16 However, we focused on the possibility that E/E', representative parameter of diastolic function, might be one of the predictors of LA thrombus prior to LA ablation, our study revealed that E/E' could not predict LA thrombus in this population.…”
Section: Predictors Of La Thrombus Prior To La Ablationmentioning
confidence: 83%
“…16, 17 Feng et al reported that AF, poor left ventricular diastolic function were independently associated with increased risk for intracardiac thrombosis in patients with amyloidosis. 16 However, we focused on the possibility that E/E', representative parameter of diastolic function, might be one of the predictors of LA thrombus prior to LA ablation, our study revealed that E/E' could not predict LA thrombus in this population.…”
Section: Predictors Of La Thrombus Prior To La Ablationmentioning
confidence: 83%
“…No intracardiac thrombus formation was detected in patients with CA, although autopsy and in vivo transesophageal echocardiogram studies suggest a prevalence rate between 15% and 30%. 34,35 Because the systematic search for thrombotic disease was outside the focus of this investigation, the reason for this discrepancy may be related to the low specificity of transesophageal echocardiogram in detecting intracardiac thrombus.…”
Section: Limitationsmentioning
confidence: 99%
“…In AL amyloid nephrotic syndrome can also contribute to hypercoagulopathy and thrombus formation. Although debated, these risks may warrant a relatively liberal use of anticoagulation as discussed below [39]- [41] [42].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Transesophageal echocardiography may help to identify patients in sinus rhythm with higher risk for thrombosis such as those with spontaneous echo contrast or low left atrial appendage velocities. A cutoff of <40cm/ sec was initially suggested [109] but this may be considerably lower (reported as 13±5cm/sec for patients with and 27±15cm/sec for patients without thrombosis) [41].…”
Section: Conventional Heart Failure Treatmentmentioning
confidence: 99%